THE IMPACT OF CORPORATE PROFITABILITY, LIQUIDITY, AND SOLVENCY INDICATORS ON SUSTAINABILITY REPORTING - Enebish, Vandandulam (Journal of Business and Innovation (Бизнес & Инноваци), 2025)
In this study, we estimated how profitability, convertibility, and solvency affect sustainability reporting based on quantitative data of first category companies on the Mongolian Stock Exchange. We also studied how corporate governance affects the sustainability reporting. The study used data on financial, governance, and sustainability reports of 14 companies for 2019-2023. The study model estimate was done with a multivariate regression analysis using a Random Effects Model. According to the results of this study, the profitability and convertibility have a positive but insignificant impact on sustainability reporting. Corporate governance was also found to be a factor that increases the positive impact on sustainability reporting.